Production of alumina-graphene-copper hybrid composites by hot pressing technique: investigation of mechanical, structural, and tribological properties - Macit, Cevher Kursat; Horlu, Merve; Tanyeri, Burak; Aksakal, Bunyamin (Springer Heidelberg, 2025)
Copper (Cu) is widely used as a dynamic electrical contact material due to the demands in the electronics, aerospace, and electric vehicle industries. In this study, a new hybrid composite material was developed by adding Graphene (Gr) and Alumina (Al2O3) at certain ratios to Copper (Cu) matrix powders produced by powder metallurgy process steps using the hot pressing technique. The structural and tribological properties of the hybrid composites that were produced were investigated. The produced Cu/Gr/Al2O3 hybrid composite showed 175% better performance in hardness and 295% better performance in coefficient of friction than the untreated Cu sample. In the weight loss values at the end of the wear test, 9 times lower weight loss occurred in the Cu/Gr/ Al2O3 hybrid composite. The study's findings indicate that the addition of Gr-Al2O3 reinforcement enhances the tribological properties of Cu matrix composites. Further research might explore the potential of incorporating novel hybrid composites.
Keywords: Powder Metallurgy; Metal matrix composites; Copper; Graphene; Aluminia; Tribology